1997
DOI: 10.1128/jb.179.24.7843-7855.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and genetic and sequence analyses of the bacteriocin 21 determinant encoded on the Enterococcus faecalis pheromone-responsive conjugative plasmid pPD1

Abstract: The pheromone-responsive conjugative plasmid pPD1 (59 kb) of Enterococcus faecalis encodes the bacteriocin 21 (bac21) determinant. Cloning, transposon insertion mutagenesis and sequence analysis of the bac21 determinant showed that an 8.5-kb fragment lying between kb 27.1 and 35.6 of the pPD1 map is required for complete expression of the bacteriocin. The 8.5-kb fragment contained nine open reading frames (ORFs), bacA to bacI, which were oriented in the same (upstream-to-downstream) direction. Transposon inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(128 citation statements)
references
References 54 publications
3
125
0
Order By: Relevance
“…This could be due to secondary interactions between intestinal microflora groups. Moreover, activity of enterocins towards Gram-negative bacteria like E. coli (Tomita et al 1997) and Vibrio cholerae has been shown (Simonetta et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to secondary interactions between intestinal microflora groups. Moreover, activity of enterocins towards Gram-negative bacteria like E. coli (Tomita et al 1997) and Vibrio cholerae has been shown (Simonetta et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent searches of the NR database using PSI-BLAST showed that homologues of g2635842 occur in Streptococcus crista (TptB), Enterococcus faecalis (BacG), Lactobacillus sake (SapE), and another in B. subtilis (g2633806). The three named proteins are putative components of ABC transport complexes (Axelsson & Holck, 1995;Correia et al, 1997;Tomita et al, 1997). All four of these proteins also have clear ®rst lipoyl motifs (M N ) and are immediately followed by regions with a high probability (>0.9) of forming coiled coils.…”
Section: Hmm Search For New Pep and Oep Family Membersmentioning
confidence: 99%
“…Mutant pHT1100 plasmids with BamHI fragment deletions within were also generated to examine the location of the bacteriocin determinant as described in Materials and Methods (Fig. 2) (47). Deletion mutant plasmids pMG1103 and pMG1104 possessed deletions of the 4.1-kbp BamHI E fragment between map positions 0 kb and 4.1 kb and the 2.2-kbp BamHI F fragment between map positions 4.1 kb and 6.3 kb, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Insertion of Tn5 (Km r ) into the cloned plasmid DNA was performed as described elsewhere (47). Target plasmid pHT1100(pAM401 containing EcoRI fragments A and H) was introduced into E. coli K-12 TH688 (with Tn5 in the thr locus) (42) by electrotransformation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation